Аспекти визначення сутності та особливостей економічної доданої вартості підприємств - Бриль, І.В. (Стратегія і механізми регулювання промислового розвитку, 2017)
Розглянуто теоретико-практичні аспекти визначення особливостей складу та здійснено порівняльний аналіз моделей розрахунків економічної доданої вартості (EVA). Доведено, що впровадження EVA на підприємствах дозволить підвищити відповідальність управлінського персоналу за прийняття рішень та максимізувати вартість бізнесу. Визначено переваги EVA на підприємствах, що дозволяють власникам управляти інвестованим капіталом та сприяють підвищенню якості оцінки загальної ефективності діяльності та капіталізації підприємства. Рассмотрены теоретико-практические аспекты определения особенностей состава и проведен сравнительный анализ моделей расчетов экономической добавленной стоимости (EVA). Доказано, что внедрение EVA на предприятиях позволит повысить ответственность управленческого персонала за принятие решений и максимизировать стоимость бизнеса. Определены преимущества EVA на предприятиях, которые позволяют владельцам управлять инвестированным капиталом и способствуют повышению качества оценки общей эффективности деятельности и капитализации предприятия. In today's economic environment, the concept of cost management is becoming more and more relevant, based on the concept of economic value added (EVA) - one of the most popular and often used options in the theory of value added. Other variations are market value added (Market Value Added, MBA), Value Added (SVA), Total Value Added (TVA).
The economic value added is a method of measuring the financial condition of an enterprise, which determines the real economic income. EVA can be calculated as the difference between net operating income after taxes and the alternative value of invested capital.
The economic added value arises at the enterprise if in the given period of time it was possible to earn the profit of the invested capital higher than the rate of return of the investor.
The essence of EVA reflects the quality of managerial decisions. The constant positive value of the EVA indicator indicates an increase in the value of the company, while a negative - about its decline. The basis of these calculations is the principle of exceeding operating profit over the value of capital.
Determining the essence of the economic value added (EVA) and the main common approaches to its calculation, it can be argued that this indicator is a criterion for assessing the profitability of the enterprise, which empowers owners to manage the invested capital. Consequently, the use of the EVA indicator will contribute to improving the quality of the assessment of the company's performance, which is also confirmed by the current data of the world ranking of the richest companies in the world whose advantages belong to the majority of high-tech companies.
Mastering the use of this technique is an important task of economic development, competitiveness and capitalization of domestic enterprises.